Impact of residual intracanal calcium hydroxide and the root canal filling techniques on apical sealant integrity - SUN Haoyu; YANG Nan; SHAN Xiaoyang; WANG Yueyue; SUN Huibin (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To compare the effects of calcium hydroxide (CH) residues in root canals and root canal filling methods on apical closure, and to provide reference for clinical selection of root canal sealing drugs and filling methods.Methods·Seventy-five permanent mandibular premolar teeth with single root canals that were extracted due to orthodontic treatment or periodontal problems were collected from the Department of Oral and Maxillofacial Surgery of the Affiliated Hospital of Qingdao University. The crowns were removed, the root canals were prepared, and the specimens were randomly assigned into 3 groups: a water-soluble calcium hydroxide group (Group A, n=30), an oil-soluble calcium hydroxide group (Group B, n=30), and an unsealed control group (Group C, n=15). After 2 weeks of sealing, Groups A and B underwent manual preparation with a #35 K-file, followed by ultrasonic agitation and irrigation of the root canal to ensure that the calcium hydroxide residue was located roughly at the root apex and that the residue was 15% to 20%. Groups A, B, and C were randomly divided into 3 groups: the iRoot SP single-tip group (Group 1), the hot compression group (Group 2), and the cold compression group (Group 3), and root canals were filled using the iRoot SP single-tip method, the hot adhesive vertical compression filling method, and the cold adhesive lateral compression filling method, respectively. A dye penetration test was used to evaluate apical microleakage, and scanning electron microscopy was used to observe the microscopic morphology of the dentin-root canal sealer interface in each group. Statistical analysis was performed using two-way ANOVA.Results·Both root canal sealing drugs and root canal filling methods affected the apical sealing, and there was an interaction between them. The effects of residual calcium hydroxide on apical closure were analyzed. The difference between Group B and Group C was statistically significant only in Group 1. There were statistically significant differences between Group A and Group C in Group 2 and Group 3, and statistically significant differences between Group A and Group B regardless of the root filling method. Among the three root filling methods, there was a statistically significant difference between Group 1 and Group 3 in Group C (P=0.013). In Group A and Group B, there were statistically significant differences between Group 2, Group 3 and Group 1 (P<0.001).Conclusion·The residual water-soluble calcium hydroxide in the root canal has a negative effect on the apical closure, but the residual oil-soluble calcium hydroxide has a small negative effect on the apical closure. iRoot SP can reduce the negative effect of residual water-soluble calcium hydroxide on root canal closure.